Ore mineralogy of the In-bearing Ayawilca Zn-Ag-Sn-Cu project, Pasco, Peru - Benites, Diego (2019)
The Ayawilca Zn-In-Ag-Sn-Cu project is located in the Central Andean polymetallic belt of Peru. It is a carbonate replacement deposit with strong similarities to porphyry-related epithermal polymetallic ("Cordilleran") deposits in the Central Andes. Forty-two ore samples were studied for petrographic and ore mineral chemistry determinations. Within an early low sulfidation stage, the most important economically and volumetrically, three generations of Fe-rich sphalerite were identified, the second being characterized by fine disseminations of chalcopyrite and the highest indium contents (up to 1.58 wt% In). Although In-bearing sphalerite is characterized by high iron contents (between ~ 9 and 32 mol. % FeS), atomic concentrations of In and Fe do not show any visible correlation. In contrast, In and Cu correlate at Cu/In = 1 (at. proportions), which is compatible with a solid solution between sphalerite and roquesite.